A case report of atrial myxoma presenting with systemic embolization and myocardial infarction. Issue 3 (11th July 2019) - Latifi, Ahmad Nawid; Ibe, Uzochukwu; Gnanaraj, Joseph
Abstract: Background: Cardiac myxomas are the most common benign primary tumour of the heart. Clinical presentation is variable and ranges from constitutional symptoms to clinical features due to intracardiac obstruction, such as mitral stenosis, coronary embolization, or systemic embolization. Surgical resection is the only effective treatment to prevent its debilitating and catastrophic complication. Case summary: A 61-year-old woman presented with an-hour history of bilateral leg pain, numbness, lightheadedness, dyspnoea, and diaphoresis. Physical exam was remarkable for pale and cold lower extremities. Arterial pulse was not palpable in the right femoral, popliteal, and posterior tibial and dorsalis pedis arteries bilaterally. Electrocardiogram demonstrated normal sinus rhythm with T-wave inversion in lead I, V2, V3, and V4. Laboratory investigations were remarkable for leucocytosis and elevated troponin. Computed tomography angiogram showed emboli with acute infarcts involving the spleen and kidneys, acute embolic occlusion of right external and internal iliac arteries, and left distal common femoral artery. She underwent emergent bilateral cut-down and femoral artery thrombectomies. Transthoracic echocardiogram demonstrated wall motion abnormalities. Computed tomography angiography of the chest revealed an atrial mass and transoesophageal echocardiography was obtained which confirmed an atrial myxoma. Coronary angiography demonstrated no significant coronary artery disease, raising the possibility of myxoma embolization to the coronary arteries as the cause of her troponin elevation and wall motion abnormality. Subsequently she underwent successful resection of the atrial myxoma. Discussion: The majority of cardiac myxomas are sporadic and arise from the left atrium as an isolated lesion in middle-aged women. Echocardiography is the diagnostic procedure of choice. The long-term survival after surgical resection is excellent and recurrence is rare.